2017
DOI: 10.1101/gad.305987.117
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent complexes of PRC1 with orthologs of BRD4 and MOZ/MORF target developmental genes in Drosophila

Abstract: Regulatory decisions in require Polycomb group (PcG) proteins to maintain the silent state and Trithorax group (TrxG) proteins to oppose silencing. Since PcG and TrxG are ubiquitous and lack apparent sequence specificity, a long-standing model is that targeting occurs via protein interactions; for instance, between repressors and PcG proteins. Instead, we found that Pc-repressive complex 1 (PRC1) purifies with coactivators Fs(1)h [female sterile (1) homeotic] and Enok/Br140 during embryogenesis. Fs(1)h is a Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 67 publications
7
41
0
Order By: Relevance
“…We next examined the binding of the recruiters and PcG proteins with respect to H3K27me3 domains. Consistent with recent studies (26)(27)(28), the binding of PcG proteins is not restricted to H3K27me3 domains. In fact, for most analyzed PcG proteins except Pc, more than 80% of peaks are outside of H3K27me3 domains (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 91%
“…We next examined the binding of the recruiters and PcG proteins with respect to H3K27me3 domains. Consistent with recent studies (26)(27)(28), the binding of PcG proteins is not restricted to H3K27me3 domains. In fact, for most analyzed PcG proteins except Pc, more than 80% of peaks are outside of H3K27me3 domains (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 91%
“…Similar to our results, Zheng et al reported that H3K4me3 modified by menin‐MLL complex (one component of TrxG complex) at the P3 and P4 promoters contributes to the robust expression of IGF2 in Hep3B cells . Another report by Kang et al showed that the choice between a transcriptionally active or silent state was associated with the enrichment of increased TrxG or PRC2 proteins at poised bivalent genes, respectively, and a decrease in TrxG impelled genes to resolve into a transition toward silencing . Taken together, these findings suggest that the expression of IGF2 is regulated by the bivalent modifications of H3K4me3 and H3K27me3 in HCC, and 91H directly binds to TrxG complex, and recruits it to the targeted P3 and P4 promoters of IGF2 gene, which further results in increased enrichment of H3K4me3 and decreased enrichment of H3K27me3 (owing to the possibility of competitive PRC2 recruitment reduction).…”
Section: Discussionsupporting
confidence: 92%
“…ChIP-seq identified two groups of PRC1/Br140 genomic binding sites that were either defined by strong H3K27me3 signal or strong H3K27ac signal (i.e., actively transcribed genes). Both groups were also marked with narrow peaks of H3K4me3 at the TSS (Kang et al 2017). These recent findings also argue for the existence of bivalent-like promoters outside of vertebrates, at least with respect to the binding of chromatin regulatory complexes, and extends the model to suggest that acetylation may be important in the resolution of bivalent protein complexes during development.…”
Section: Discussionsupporting
confidence: 63%